Introduction to information processing - Robichaud, Beryl; Muscat, Eugune J.;Hall, Alix-Marie (New York : McGraw Hill Education, 1989)
The textbook presents the basics of modern methods of processing data, while assuming little or no familiarity with information processing on the part of the instructor or the student.
Part 1. Concepts of information processing and computers -- Part 2. Computer hardware -- Part 3. Computer information systems -- Part 4. Computer programming and software -- Part 5. Opportunities in information processing -- Part 6. The future.
Includes index.
Keywords: ELECTRONIC DATA PROCESSING